Ectopic pregnancy after hysterectomy may not be so uncommon: A case report and review of the literature - Donald L. Fylstra (Elsevier, 2015)
Background: Ectopic pregnancy after hysterectomy is a very uncommon event, but its frequency is increasing. Since first reported by Wendler in 1895, 71 cases of post-hysterectomy have been reported. Case: A woman, 2 years after an abdominal supracervical hysterectomy, presented with a ruptured fallopian tube ectopic pregnancy. Conclusion: Any woman, even after hysterectomy but with ovaries in situ, who presents with an acute abdomen or abdominal-pelvic pain should be screened for pregnancy. Keywords: Ectopic pregnancy, Hysterectomy, Vaginal-peritoneal fistula